Effects of Gintonin-Enriched Fraction on Methylmercury-Induced Neurotoxicity and Organ Methylmercury Elimination - Kim, Hyeon-Joong; Choi, Sun-Hye; Lee, Na-Eun; Cho, Hee-Jung; Rhim, Hyewhon; Kim, Hyoung-Chun; Hwang, Sung-Hee; Nah, Seung-Yeol (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Gintonin is a newly discovered ingredient of ginseng and plays an exogenous ligand for G protein-coupled lysophosphatidic acid receptors. We previously showed that gintonin exhibits diverse effects from neurotransmitter release to improvement of Alzheimer's disease-related cognitive dysfunctions. However, previous studies did not show whether gintonin has protective effects against environmental heavy metal. We investigated the effects of gintonin-enriched fraction (GEF) on methylmercury (MeHg)-induced neurotoxicity and learning and memory dysfunction and on organ MeHg elimination. Using hippocampal neural progenitor cells (hNPCs) and mice we examined the effects of GEF on MeHg-induced hippocampal NPC neurotoxicity, on formation of reactive oxygen species (ROS), and on in vivo learning and memory functions after acute MeHg exposure. Treatment of GEF to hNPCs attenuated MeHg-induced neurotoxicity with concentration- and time-dependent manner. GEF treatment inhibited MeHg- and ROS inducer-induced ROS formations. Long-term treatment of GEF also improved MeHg-induced learning and memory dysfunctions. Oral administration of GEF decreased the concentrations of MeHg in blood, brain, liver, and kidney. This is the first report that GEF attenuated MeHg-induced in vitro and in vivo neurotoxicities through LPA (lysophosphatidic acids) receptor-independent manner and increased organ MeHg elimination. GEF-mediated neuroprotection might achieve via inhibition of ROS formation and facilitation of MeHg elimination from body.